2008
DOI: 10.1027/0044-3409.216.3.127
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Assessment

Abstract: Developmental diagnostics has a long-standing tradition of more than 100 years and is closely connected with the assessment of children’s abilities, for instance, intelligence. It aims at providing differentiated analysis of developmental status, at contrasting normal and abnormal development, and at evaluating the potential for further development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…It is usually suggested that difficulty parameters of the given test items are conducted so as to monotonically increase with age (Petermann and Macha, 2005, 2008). Just as developmental testing has to be carried out in an age-based manner, corresponding difficulty parameters have to be calculated for each single age group under examination.…”
Section: Which Implications Are There For Test Development and Test Cmentioning
confidence: 99%
“…It is usually suggested that difficulty parameters of the given test items are conducted so as to monotonically increase with age (Petermann and Macha, 2005, 2008). Just as developmental testing has to be carried out in an age-based manner, corresponding difficulty parameters have to be calculated for each single age group under examination.…”
Section: Which Implications Are There For Test Development and Test Cmentioning
confidence: 99%
“…Sensitivity to change is also an important test characteristic when an assessment will be repeated for the purpose of progress monitoring (Dale & Salt, 2007). A test that is sensitive to child development is expected to yield higher scores in older children, except in cases where something has occurred that would account for regression (Petermann & Macha, 2008). When age is not predictive of motor scores for children who are visually impaired, it is an indicator that the assessment is not valid for this population (Houwen et al, 2010, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%